Discriminating the non-coordination between ecosystem service value and economic development and its spatial characteristics in central Yunnan urban agglomeration in the recent 30 years - Li, Anlin; Yang, Yehua; Niu, Lede; Luo, Haichao; Chi, Hengxing (Frontiers in Ecology and Evolution, 2024)
Environmental issues have become one of the important topics affecting China and the world. As the world’s most populous country and the second-largest economy, China’s environmental conditions have significant impacts on global ecosystems and sustainable development. To accurately determine the relationship between economic development and the environment, explore the non-coordination and spatial characteristics between the two, and promote regional sustainable development. This study is based on land-use data from four periods: 1990, 2000, 2010, and 2020. It uses the dynamic measurement and value equivalent method to explore the characteristics of land-use changes and measure the value of ecosystem services in the Central Yunnan Urban Agglomeration. At the same time, the study uses the non-coordination degree model and hotspot analysis tools to identify the non-coordination between Ecosystem Service Value and economic development (Gross Domestic Product), and explore the spatial characteristics between them. The research results show that: (1) The main land-use types include cultivated land, forest land, and grassland, which account for more than 90% of the total proportion. The land types with a small proportion in the region are water areas, construction land, and unused land. (2) The development level of ecosystem service value presents four types of changes: fluctuating increase, fluctuating decrease, continuous increase, and continuous decrease. The regional spatial distribution shows obvious regional heterogeneity, overall presenting a spatial distribution pattern of “low in the middle, high around.” (3) The average index of non-coordination degree from 1990 to 2020 is 0.591, 0.635, 0.584, and 0.565, showing a coordinated non-coordination coupling type. The regional space presents a spatial pattern of “high in the central and western regions, low in the northeastern and southern regions.” (4) The hotspots of non-coordination are mainly concentrated in the central and northwest regions of the Central Yunnan Urban Agglomeration, while the coldspots of non-coordination are mainly distributed in the northeastern, western, and southern regions of the Central Yunnan Urban Agglomeration, showing a regular agglomeration distribution. This study suggests that it is necessary to balance and coordinate the relationship between regional economic development and the environment.